The Useage of Visceral Therapy after Open Cholecystectomy Surgery – Case Study - Rogala, Adrian; Brzuszkiewicz-Kuzmicka, Grazyna (Archives of Clinical and Medical Case Reports, 2020)
Introduction: There are many gallbladder disorders, but cholelithiasis (cholelithiasis) is the most common. In Europe, cholelithiasis affect around 10%-15% of the population. In the US, 700,000 people undergo cholecystectomy every year. Surgical intervention of the abdominal cavity contributes to the disorganization of the connective tissue. In the current literature, there are few reports showing the relationship between intra-abdominal tension and non-specific cervical pain, or gastric symptoms. Objective: The aim of the study is to present the impact of visceral therapy in the patient who has undergone open cholecystectomy. Material and Methods: 53-year-old female after removal of the gallbladder, with cervical spine pains, upper limb paresthesia and gastric symptoms. Diagnostic imaging in the form of an x-ray showed minor degenerative changes and slight discopathy. Blood examination showed no abnormalities. The patient was assessed by reliable and valid questionnaires such as: VAS, Laitinen, GSRS, QOLRAD, Bristol Stool Formation Scales. Results: After visceral therapy the following results were obtained: GSRS scale=20/105 pt., QOLRAD scale=169/175 pt., Laitinen scale=0/12 and the occurrence of stool No. 5 on the Bristol scale. Conclusion: Visceral therapy may be helpful in the therapy of patients after open cholecystectomy. Postoperative scars can affect the functions of internal organs, and their dysfunction can affect the musculoskeletal system.